Aliphatic amines in Antarctic CR2, CM2, and CM1/2 carbonaceous chondrites. (15th September 2016) - Aponte, José C.; McLain, Hannah L.; Dworkin, Jason P.; Elsila, Jamie E.
Abstract: Meteoritic water-soluble organic compounds provide a unique record of the processes that occurred during the formation of the solar system and the chemistry preceding the origins of life on Earth. We have investigated the molecular distribution, compound-specific δ 13 C isotopic ratios and enantiomeric compositions of aliphatic monoamines present in the hot acid–water extracts of the carbonaceous chondrites LAP 02342 (CR2), GRA 95229 (CR2), LON 94101 (CM2), LEW 90500 (CM2), and ALH 83100 (CM1/2). Analyses of the concentration of monoamines in these meteorites revealed: (a) the CR2 chondrites studied here contain higher concentrations of monoamines relative to the analyzed CM2 chondrites; (b) the concentration of monoamines decreases with increasing carbon number; and (c) isopropylamine is the most abundant monoamine in these CR2 chondrites, while methylamine is the most abundant amine species in these CM2 and CM1/2 chondrites. The δ 13 C values of monoamines in CR2 chondrite do not correlate with the number of carbon atoms; however, in CM2 and CM1/2 chondrites, the 13 C enrichment decreases with increasing monoamine carbon number. The δ 13 C values of methylamine in CR2 chondrites ranged from −1 to +10‰, while in CM2 and CM1/2 chondrites the δ 13 C values of methylamine ranged from +41 to +59‰. We also observed racemic compositions of sec -butylamine, 3-methyl-2-butylamine, and sec -pentylamine in the studied carbonaceous chondrites. Additionally, we compared the abundance and δ 13 C isotopic composition of monoamines to those of their structurally related amino acids. We found that monoamines are less abundant than amino acids in CR2 chondrites, with the opposite being true in CM2 and CM1/2 chondrites. We used these collective data to evaluate different primordial synthetic pathways for monoamines in carbonaceous chondrites and to understand the potential common origins these molecules may share with meteoritic amino acids.